RELATIONSHIP BETWEEN THE SEVERITY OF LOWER THIRD MOLAR IMPACTION ON POST-ODONTECTOMY PAIN INTENSITY - Tammama, Tichvy; Puti Rahmayani Sabirin, Indah; Dwi Kusuma, Feliana (Fakultas Kedokteran Gigi Unjani, 2024)
The third molar is the last tooth to erupt, so it often experiences impaction with varying severity. Impacted teeth can cause various problems, so they need to be removed. Extraction of the third molar, namely odontectomy, sometimes causes postoperative complications; one of the most common is pain. The purpose of this study was to determine the relationship between the severity of impaction of the lower third molar and the intensity of pain after odontectomy. This study is an observational analytical study with a cross-sectional approach. The sampling method used was non-random, using the purposive sampling technique, for patients who came to the oral surgery clinic of Gunung Jati Regional Hospital, Cirebon, and had undergone odontectomy of the lower third molar. This study assessed the severity of impaction based on the Pedersen classification with the help of panoramic images into mild, moderate, and severe. The intensity of pain after odontectomy was measured using the NRS score into mild, moderate, and severe. The results showed that of the 37 patients who underwent odontectomy, the majority had moderate impaction severity in 24 patients (64.9%) and experienced moderate pain intensity post-odontectomy in 14 patients (37.8%). Spearman's correlation test showed a p-value of 0.530 (p> 0.05). there is no correlation between the severity of lower third molar impaction and postoperative pain intensity. DOI : 10.54052/jhds.v4n2.p191-202